Autodidatismo na Dança: outros caminhos possíveis de pensar formação - CARMO, Karla Nayara Ferreira do (2022)
This research is part of my trajectory on the dance course that happens in the alternative spaces and in a self-taught way until I join the Universidade Federal do Pará to study a Degree in Dance, when I come across different training processes and then reflect the paths followed by me until that moment, arising questions pertinent to what concerns the possibilities of thinking the formation of a dancing body. The relevance of this work lies in the plurality of the formative processes of the bodies and their different ways of producing knowledge to effect the places of non academic knowledge, such as those obtained from our cultural and daily life. These knowledge, for me, dialogue with scientific knowledge and have the same importance in the formation of a subject, so I propose to reflect in this work the importance and legitimation of the different knowledge within the formative process, in which the knowledge produced in a self-taught way are important, to the same extent, as those produced in academic circles. The different formative process are not empty, just as the dance is not empty. This research assumes the methodological approach of autoethnography, because it reveals the particular knowledge and experiences within the phenomenon, so I propose to bring to this work my personal experiences in the context of the relationship with the culture in which I am inserted and my practices in this place as form of knowledge. We feed on life and everything that surrounds this inescapable flow of affectations and to give power to our dance, a power that is related to the different knowledge that we have access throughout the formative walk, thus, there is no possibility of a standardization of the dance training process, since each body is immersed in different cultural processes and their experiences are different.